Prenatal management of congenital cystic adenomatoid lung malformation, macrocystic type. Report of a series of cases treated in utero in Peru and review of the literature - Ventura Laveriano, Walter (2018)
We report a series of three cases with prenatal diagnosis of congenital cystic adenomatoid malformation of the lung, macrocystic type, treated in utero with thoraco-amniotic shunting. This highly specialized intervention is feasible in our local setting. The three cases survived. A mini-review of this condition is presented and an algorithm of prenatal management is proposed.